1994
DOI: 10.1007/bf01857920
|View full text |Cite
|
Sign up to set email alerts
|

Stress, depression, and anxiety predict average symptom severity and daily symptom fluctuation in systemic lupus erythematosus

Abstract: Forty-one subjects diagnosed with systemic lupus erythematosus (SLE) were recruited from across the United States. Regressions were conducted to evaluate the relation among stress, depression, anxiety, anger, and SLE symptom complaints. Negative weighting of major life events predicted symptom history. Significant hierarchical regressions using negative weighting of major life events, impact of daily stress, depression, anxiety, and anger were found for severity of joint pain, abdominal distress, and rash. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 22 publications
(22 reference statements)
2
44
0
3
Order By: Relevance
“…These data further support previous reports of a relationship between psychosocial factors and an exacerbation of disease activity in SLE. Previously, Adams et al [1]also suggested an association between daily stress, depression, and anxiety with self-reported symptomatology in SLE patients. In contrast, Wekking et al [2]showed no relationship between laboratory parameters and subjective ratings of psychological and physical status in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data further support previous reports of a relationship between psychosocial factors and an exacerbation of disease activity in SLE. Previously, Adams et al [1]also suggested an association between daily stress, depression, and anxiety with self-reported symptomatology in SLE patients. In contrast, Wekking et al [2]showed no relationship between laboratory parameters and subjective ratings of psychological and physical status in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies performed so far on psychological stress and SLE suggest associations between daily stress, depression, and anxiety with self-reported symptoms in these patients [1], while others failed to find evidence for such relationships [2]. Additionally, clinical exacerbations were not observed in patients with SLE after a major environmental stressor such as an earthquake [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stress has been described as a trigger and may worsen the patient’s condition in cases of SLE [1,2,3,4,5,6,7,8,9,10] and other autoimmune diseases [11,12]. Some studies [3,4,5,6,7,8,9,10] have shown that chronic stress (low-intensity events repeated over time) is most strongly linked to deterioration in patients with the disease. Peralta-Ramírez et al [8] evaluated 58 patients with lupus (46 with SLE and 12 with CCL) for 6 months and found that chronic stress worsened the symptoms of the disease to the greatest degree, and this was observed in up to 74% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Existem seis estudos prospectivos sobre esse tema, mais adequados na verificação da correlação estudada, mas que diferem bastante quanto à metodologia empregada (44)(45)(46)(47)(48)(49) . Wekking et al seguiram 13 pacientes com LES durante um ano e mostraram que a freqüência e a intensidade de estressores diários correlacionam-se com depressão e ansiedade e número de atividades sociais, mas não com alguns parâmetros de atividade da doença (alterações laboratoriais, como hemograma e anticorpos, escalas de sintomas ou de interferência em atividades cotidianas).…”
Section: Inluência Do Estresse No Lesunclassified
“…Apesar de serem comparados a um grupo de pacientes com artrite reumatóide como controle, o índice de drop-out deste estudo foi muito grande pois apenas cinco pacientes completaram todos os exames laboratoriais (44) . Um outro estudo, realizado através da aplicação de questionários de preenchimento diário por quase dois meses e remetidos via postal, verificou que o estresse estava associado aos sintomas de depressão, raiva e ansiedade e ao aumento da sintomatologia da doença em 41 pacientes, embora não tenha usado medidas confiáveis de piora da doença ou de presença de estressores (45) . Ambos os estudos apresentam em comum a relação do estresse com medidas subjetivas de sofrimento do paciente.…”
Section: Inluência Do Estresse No Lesunclassified